The unfolded protein response regulates hepatic autophagy by sXBP1-mediated activation of TFEB. Issue 8 (3rd August 2021) - Zhang, Zeyuan; Qian, Qingwen; Li, Mark; Shao, Fan; Ding, Wen-Xing; Lira, Vitor A.; Chen, Sophia X.; Sebag, Sara C.; Hotamisligil, Gökhan S.; Cao, Huojun; Yang, Ling
ABSTRACT: Defective macroautophagy/autophagy and a failure to initiate the adaptive unfolded protein response (UPR) in response to the endoplasmic reticulum (ER) stress contributes to obesity-associated metabolic dysfunction. However, whether and how unresolved ER stress leads to defects in the autophagy pathway and to the progression of obesity-associated hepatic pathologies remains unclear. Obesity suppresses the expression of hepatic spliced XBP1 (X-box binding protein 1; sXBP1), the key transcription factor that promotes the adaptive UPR. Our RNA-seq analysis revealed that sXBP1 regulates genes involved in lysosomal function in the liver under fasting conditions. Chromatin immunoprecipitation (ChIP) analyzes of both primary hepatocytes and whole livers further showed that sXBP1 occupies the −743 to −523 site of the promoter of Tfeb (transcription factor EB), a master regulator of autophagy and lysosome biogenesis. Notably, this occupancy was significantly reduced in livers from patients with steatosis. In mice, hepatic deletion of Xbp1 ( xbp1 LKO) suppressed the transcription of Tfeb as well as autophagy, whereas hepatic overexpression of s Xbp1 enhanced Tfeb transcription and autophagy. Moreover, overexpression of Tfeb in the xbp1 LKO mouse liver ameliorated glucose intolerance and steatosis in mice with diet-induced obesity (DIO). Conversely, loss of TFEB function impaired the protective role of sXBP1 in hepatic steatosis in mice with DIO. These data indicate that sXBP1- Tfeb signaling has direct functional consequences in the context of obesity. Collectively, our data provide novel insight into how two organelle stress responses are integrated to protect against obesity-associated metabolic dysfunction. Abbreviations: AAV8: adeno-associated virus serotype 8; ACTB: actin, beta; ANOVA: analysis of variance; ATF6: activating transcription factor-6; ATG: autophagy related; BECN1: beclin 1; BMI: body mass index; ChIP: chromatin immunoprecipitation; CLEAR: coordinated lysosomal expression and regulation; Cre: cre recombinase; DIO: diet-induced obesity; EBSS: Earle's balanced salt solution; EIF2AK3/PERK: eukaryotic translation initiation factor 2 alpha kinase 3; ER: endoplasmic reticulum; ERN1/IRE1: endoplasmic reticulum (ER) to nucleus signaling 1; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; HFD: high-fat diet; h: hours; HSCs: hepatic stellate cells; INS: insulin; L/A: ammonium chloride and leupeptin; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; mRNA: messenger RNA; NAFLD: nonalcoholic fatty liver disease; NASH: nonalcoholic steatohepatitis; RD: regular diet; RFP: red fluorescent protein; SERPINA7/TBG: serpin family A member 7; SQSTM1/p62: sequestome 1; s Xbp1 LOE: liver-specific overexpression of spliced Xbp1 ; TFEB: transcription factor EB; TG: thapsigargin; TN: tunicamycin; UPR: unfolded protein response; wks: weeks; WT: wild type; XBP1: X-box binding protein 1; xbp1 LKO: liver-specific Xbp1 knockout.